A long-life nanostructured thermal barrier coating with low thermal conductivity and high thermal expansion coefficient and a preparation method thereof

CN121085316BActive Publication Date: 2026-10-30HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511230748.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-30
Publication Date
2026-10-30
Estimated Expiration
2045-08-30

AI Technical Summary

Technical Problem

[0005]本发明针对现有热障涂层材料存在的热导率较高、热膨胀系数与基体匹配性不足、高温相稳定性有待提升等问题,提供了一种通过五元稀土协同掺杂调控晶体结构与缺陷分布的低热导高热膨胀系数的长寿命纳米结构热障涂层及其制备方法,通过五元稀土协同掺杂与全流程工艺参数优化,构建“晶格稳定-氧化抑制-烧结延缓”三重防护机制,显著提升涂层的高温服役寿命,以满足航空航天、能源动力等领域高温部件对涂层材料高隔热性、高可靠性的需求

Benefits of technology

[0017]1)材料性能优势:多元稀土协同掺杂(Gd3+、Yb3+、La3+、Ce4+、Y3+)通过电荷补偿效应调控氧空位,形成缺陷散射中心,结合纳米结构的多重声子散射机制显著降低了声子传输效率,使1000℃热导率≤1.2 W·m-1·K-1,较传统8YSZ降低30%以上。同时,稀土离子半径差异引发晶格畸变,导致晶格膨胀,晶格能降低,有利于增大热膨胀系数,1200℃热膨胀系数≥11.2×10-6 K-1,与镍基合金基体匹配性提升,减少热应力集中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121085316B_ABST
    Figure CN121085316B_ABST
Patent Text Reader

Abstract

The application discloses a long-life nano-structure thermal barrier coating with low thermal conductivity and high thermal expansion coefficient and a preparation method thereof, and the thermal barrier coating comprises a substrate, a metal bonding layer and a ceramic surface layer. 1‑x (Gd,Yb,La,Ce,Y) x O 2‑δ , x=0.12~0.15, the doping amount of single rare earth ion is not less than 1 mol%, the doping amounts of Gd 3+ and Yb 3+ are respectively 2~3 mol%, and the oxygen vacancy concentration delta is controlled by the charge difference of Ce 4+ , Gd 3+ , Yb 3+ , La 3+ and Y 3+ . The thermal barrier coating of the application has no peeling after being kept at 1100 DEG C for 100 hours, the phase of the ceramic surface layer is stable and has no change, and is a single tetragonal phase; and the average TGO growth rate of the thermal barrier coating is less than 1.4 mg.cm ‑2 .h ‑1 -1 within 100 hours at 1100 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-temperature protective coating, specifically to a pentagonal rare-earth-doped zirconium oxide-based long-life nanostructure thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion, and its preparation method. Background Technology

[0002] Thermal barrier coatings (TBCs) are a core protective technology for high-temperature equipment, and their ceramic insulation layers typically employ 6-8 wt% Y₂O₃-stabilized ZrO₂ (YSZ). However, traditional YSZ coatings suffer from significant drawbacks during long-term high-temperature service: 1) Insufficient phase stability: Under high temperatures and long-term operation, YSZ is prone to a transformation from a tetragonal phase to a monoclinic phase, accompanied by approximately 4% volume expansion, leading to internal stress concentration and accelerating crack initiation and propagation; 2) Sintering densification issues: During long-term operation above 1000℃, the porosity of the YSZ coating decreases sharply, reducing its thermal insulation performance and strain tolerance, failing to effectively alleviate thermal shock stress, and making the coating prone to peeling and failure; 3) Limited oxidation resistance: At high temperatures, thermally grown oxides (TGOs) easily form at the interface between the YSZ coating and the adhesive layer. When the TGO thickness exceeds a critical value (typically 8-10 μm), it triggers enormous interfacial stress, leading to coating peeling. These defects limit the service life of YSZ coatings on high-temperature components.

[0003] Studies have shown that multi-element rare earth co-doping can synergistically optimize the performance of zirconium oxide: large-radius ions (such as La) 3+ Ce 4+ Gd 3 + Increasing lattice distortion reduces the mean free path of phonons, decreases thermal conductivity, and simultaneously increases the coefficient of thermal expansion, thus alleviating thermal stress; small-radius ions (such as Y) 3+ Yb 3+ ) synergistically stabilizes the tetragonal phase (t'-ZrO2), solving the high-temperature instability problem of a single stabilizer; in addition, Gd 3+ and La 3+ Doping with elements such as Ca, Mg, Sr, Sc, Ce, Gd, La, Y, Yb, and Sm can inhibit grain growth and delay sintering densification. CN 115124339 A discloses a multi-element high-entropy doped zirconia-based ceramic material, its preparation method, and its application. It is prepared by equimolar doping of five or more elements selected from Ca, Mg, Sr, Sc, Ce, Gd, La, Y, Yb, and Sm into a zirconia matrix. It shows better improvement in anti-sintering ability, reduced thermal conductivity, and high-temperature phase stability compared to traditional YSZ materials. However, it ignores the differences in the modification effect of different dopants on zirconia and does not design the doping ratio of different dopants, resulting in the thermal expansion coefficient and fracture toughness of the material still being inferior to those of YSZ materials.

[0004] Current research lacks a systematic understanding of issues such as the total doping amount and the proportion of different doping elements, and the comprehensive performance of multi-element doped zirconia systems requires further development. Furthermore, for zirconia-based nanostructured thermal barrier coating systems, a complete technical solution encompassing synergistic doping of five rare earth elements (Gd, Yb, La, Ce, Y), nanostructure control, and optimization of spraying process parameters has not yet been established. Specifically: 1) The synergistic effect of single rare earth ion doping amount and total doping amount needs to be clarified to resolve the contradiction between charge balance and lattice distortion; 2) A parameter combination for wet ball milling, spray drying, and sintering needs to be established to achieve controllable preparation of nanocrystals (<100nm) and a single tetragonal phase structure; 3) The service life of the coating system at high temperatures needs to be improved through gradient design of the adhesive layer thickness and ceramic layer thickness, combined with optimization of plasma spraying parameters. Summary of the Invention

[0005] This invention addresses the problems of high thermal conductivity, insufficient matching of thermal expansion coefficient with the substrate, and the need to improve high-temperature phase stability in existing thermal barrier coating materials. It provides a long-life nanostructured thermal barrier coating with low thermal conductivity and high thermal expansion coefficient, achieved through pentagonal rare earth co-doping to regulate crystal structure and defect distribution, along with its preparation method. By optimizing pentagonal rare earth co-doping and the entire process parameters, a triple protection mechanism of "lattice stability, oxidation inhibition, and sintering delay" is constructed, significantly improving the high-temperature service life of the coating to meet the high thermal insulation and high reliability requirements of high-temperature components in aerospace, energy, and other fields. This invention breaks through the performance bottlenecks of traditional thermal barrier coatings and has significant technological advancements and engineering application value.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] A five-element rare earth-doped zirconium oxide nanostructured ceramic material with the chemical formula Zr 1-x (Gd,Yb,La,Ce,Y) x O 2-δ x = 0.12~0.15, meaning the total rare earth ion doping amount is 12~15 mol%, of which the doping amount of a single rare earth ion is not less than 1 mol%. Gd 3+ and Yb 3+ The doping amounts were 2~3 mol%, Y 3+ The doping concentration is less than 4 mol%, through Ce 4+ With trivalent rare earth ions (Gd 3+ Yb 3+ La 3+ Y 3+The charge difference regulates the oxygen vacancy concentration δ, forming a specific defect structure; the microstructure of the ceramic material satisfies the following: average grain size < 100 nm, and the phase is a single tetragonal zirconium oxide; through differential control of different rare earth ion doping amounts, the ceramic material achieves comprehensive optimization of low thermal conductivity and high thermal expansion coefficient, with a thermal conductivity ≤ 1.2 W·m at 1000℃. -1 ·K -1 The coefficient of thermal expansion at 1200℃ is ≥11.2×10⁻⁶. -6 K -1 Fracture toughness at room temperature > 4.5 MPa·m 1 / 2 .

[0008] A preparation process for the above-mentioned pentagonal rare earth-doped zirconium oxide nanostructured ceramic material includes the following steps:

[0009] Step A1, Slurry Preparation: Gd2O3, Yb2O3, La2O3, CeO2, and Y2O3 nanoparticles with a purity ≥99.9% and an average grain size <100 nm are mixed into ZrO2 nanoparticles. A binder, dispersant, and deionized water are added, and the mixture is ball-milled at 400-800 rpm for 4-12 h using zirconia ball milling media to obtain a uniformly dispersed slurry. The slurry has the following characteristics: a solid content of 30-60 wt%, preferably 45-55 wt%; a binder of polyvinyl alcohol (PVA) added at 0.5-2 wt% of the total nanoparticles, preferably not exceeding 1 wt%; a dispersant of ammonium citrate added at 0.5-3 wt% of the total nanoparticles, preferably not less than 1 wt%; a ball-to-particle ratio of 1-3:1; and a water-to-particle ratio of 0.8-2:1.

[0010] Step A2, spray drying: The slurry is spray dried through a spray dryer to obtain spherical or apple-shaped dried powder. Its secondary structure retains the nanostructure of the raw material. After the powder is completely dried at 80~100℃, it is passed through a 200~400 mesh sieve for subsequent solid-phase synthesis. The peristaltic pump speed is controlled at 30~50 rpm, the fan speed at 30~40 rpm, and the air inlet temperature at 240~260℃.

[0011] Step A3, Solid-phase synthesis: The dried powder is sintered at 1200~1300℃ for 1~2 h in an atmospheric atmosphere to obtain a pentagonal rare earth-doped zirconia nanostructured ceramic material with the target microstructure and properties. The primary structure of the pentagonal rare earth-doped zirconia nanostructured ceramic material is a spherical or apple-shaped structure, and the secondary structure maintains a nanoscale structure. After passing through a 200~400 mesh sieve, the particle size is 38~75μm, and the flowability is 130~150 s / 50g (refer to GB / T 1482-2022).

[0012] A long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion comprises the following structure: 1) a substrate composed of a high-temperature nickel-based alloy GH3230; 2) a metal bonding layer formed on the surface of the substrate, composed of NiCoCrAlY with a thickness of 100~120μm, bonded to the substrate via high-velocity plasma flame (HVOF) technology; and 3) a ceramic surface layer formed on the metal bonding layer, composed of a pentagonal rare-earth-doped zirconium oxide nanostructured ceramic material with the chemical formula Zr. 1-x (Gd,Yb,La,Ce,Y) x O 2-δ x = 0.12~0.15, meaning the total rare earth ion doping amount is 12~15 mol%, of which the doping amount of a single rare earth ion is not less than 1 mol%. Gd 3+ and Yb 3+ The doping amounts were 2~3 mol%, Y 3+ The doping concentration is less than 4 mol%, through Ce 4+ With trivalent rare earth ions (Gd 3+ Yb 3+ La 3+ Y 3+ The charge difference regulates the oxygen vacancy concentration δ, resulting in a single tetragonal zirconia phase with a thickness of 200-300 μm, bonded to a metal bonding layer via plasma spraying. The thermal barrier coating exhibits the following characteristics: 1) The ceramic surface layer displays a "dual-mode" structure consisting of an unmelted region retaining the nanostructure and a molten region undergoing recrystallization; 2) The porosity of the ceramic surface layer does not exceed 15%; 3) After holding at 1100℃ for 100 h, the coating shows no peeling, and the ceramic surface layer phase remains stable and unchanged, exhibiting a single tetragonal phase; 4) The average TGO growth rate of the thermal barrier coating at 1100℃ for 100 h is less than 1.4 mg·cm³. -2 ·h -1 .

[0013] A process for preparing the above-mentioned long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion includes the following steps:

[0014] Step B1, Preparation of substrate and adhesive layer: NiCoCrAlY powder is sprayed onto the substrate surface using HVOF technology to form a metal adhesive layer. The process parameters are as follows: argon flow rate of shielding gas is 340~360 NLPM, methane / oxygen flow rates are 170~180 NLPM / 240~250 NLPM, nitrogen flow rate of carrier gas is 3~5 NLPM, powder feed rate is 30~40 g / min, and spraying distance is 240~260 mm.

[0015] Step B2, Ceramic Surface Layer Preparation: Using pentagonal rare earth-doped zirconium oxide powder as feedstock, the ceramic surface layer is sprayed onto the surface of the adhesive layer using an atmospheric plasma spraying process to form a complete, long-life nanostructured thermal barrier coating. The process parameters are: current 550~600 A, voltage 65~75 V, main gas argon flow rate 40~42 SLPM, auxiliary gas hydrogen flow rate 11~13 SLPM, carrier gas argon flow rate 2~3 SLPM, and powder feeding rate 20~30 rpm.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1) Material performance advantages: Multi-element rare earth synergistic doping (Gd 3+ Yb 3+ La 3+ Ce 4+ Y 3+ By modulating oxygen vacancies through charge compensation effects to form defect scattering centers, and combining this with the multiple phonon scattering mechanism of nanostructures, the phonon transmission efficiency is significantly reduced, resulting in a thermal conductivity of ≤1.2 W·m at 1000℃. -1 ·K -1 This reduces the efficiency by more than 30% compared to traditional 8YSZ. Simultaneously, the difference in rare earth ion radii induces lattice distortion, leading to lattice expansion and a decrease in lattice energy, which is beneficial for increasing the coefficient of thermal expansion; the coefficient of thermal expansion at 1200℃ is ≥11.2×10⁻⁶. -6 K -1 It improves compatibility with nickel-based alloy matrix and reduces thermal stress concentration.

[0018] 2) Advantages of the preparation process: The wet ball milling combined with the spray drying process achieves uniform dispersion and morphology control of nanoparticles. The resulting spherical powder has excellent flowability (130~150 s / 50g), which is suitable for plasma spraying feeding requirements. Low temperature short time sintering (1200℃, 1h) inhibits grain coarsening, retains the nanostructure, and avoids the phase transformation and performance degradation caused by traditional high temperature sintering.

[0019] 3) Advantages of the coating system: The binder layer is prepared using HVOF technology, forming a dense (porosity <1%) and low-oxidation state (oxygen content <0.8wt%), which inhibits the uncontrolled growth of TGO. The ceramic surface layer, through precise control of plasma spraying parameters, forms a nanostructure coating with a "dual-modal" distribution of nano-regions and molten regions, and controls the porosity of the ceramic surface layer to 10~15%. This structure is conducive to further reducing the thermal conductivity of the coating, inhibiting the excessively rapid growth of TGO, and absorbing stress. The coating system does not peel off during long-term operation at high temperature (1100℃, 100h), the phase remains stable and unchanged, maintaining a single tetragonal phase, and the average growth rate of TGO is <1.4 mg·cm⁻¹. -2 ·h -1 It meets the requirements of harsh high-temperature service environments.

[0020] In summary, this invention, through the synergistic effect of material composition design, microstructure control, and preparation process optimization, breaks through the bottlenecks of traditional thermal barrier coatings in terms of thermal insulation and reliability, and provides an effective solution for extending the lifespan of high-temperature components. Attached Figure Description

[0021] Figure 1 These are the primary and secondary structures of the five rare earth-doped zirconium oxide powder with low thermal conductivity and high thermal expansion coefficient prepared in Example 1;

[0022] Figure 2 This is the XRD pattern of the five rare earth-doped zirconium oxide powder with low thermal conductivity and high thermal expansion coefficient prepared in Example 1;

[0023] Figure 3 These are the primary and secondary structures of the five rare earth-doped zirconium oxide powder with low thermal conductivity and high thermal expansion coefficient prepared in Example 2;

[0024] Figure 4 This is the XRD pattern of the five rare earth-doped zirconium oxide powder with low thermal conductivity and high thermal expansion coefficient prepared in Example 2;

[0025] Figure 5 This is the cross-sectional microstructure of the pentagonal rare earth-doped zirconium oxide coating prepared in Example 3;

[0026] Figure 6 These are the XRD patterns of the pentagonal rare earth-doped zirconium oxide coating prepared in Example 3 and the traditional YSZ coating;

[0027] Figure 7 The thermal conductivity of the pentagonal rare earth doped zirconium oxide coating prepared in Examples 3 and 4 and the conventional YSZ coating from room temperature to 1000°C;

[0028] Figure 8 The coefficients of thermal expansion of the pentagonal rare earth-doped zirconium oxide coatings prepared in Examples 3 and 4 and the conventional YSZ coating at 200 to 1200 °C;

[0029] Figure 9 This is the cross-sectional microstructure of the pentagonal rare earth-doped zirconium oxide coating prepared in Example 4;

[0030] Figure 10 These are the XRD patterns of the pentagonal rare earth-doped zirconium oxide coating prepared in Example 4 and the traditional YSZ coating;

[0031] Figure 11 This is the flowchart of the isothermal oxidation experiment used in Example 5;

[0032] Figure 12These are macroscopic morphology photographs of the surfaces of the five rare earth-doped zirconium oxide nanostructure thermal barrier coating and YSZ coating prepared in Examples 3 and 4 after being kept at 1100℃ for different holding times.

[0033] Figure 13 The changes in TGO per unit area of ​​the five rare earth-doped zirconium oxide nanostructure thermal barrier coating and YSZ coating prepared in Examples 3 and 4 after different holding times at 1100℃ are shown.

[0034] Figure 14 The cross-sectional morphology of the five rare earth-doped zirconium oxide nanostructure thermal barrier coating and YSZ coating prepared in Examples 3 and 4 after being kept at 1100℃ for 100 h.

[0035] Figure 15 The images show the XRD patterns of the five rare-earth-doped zirconium oxide nanostructure thermal barrier coating and YSZ coating prepared in Examples 3 and 4 after being kept at 1100℃ for 100 h. Detailed Implementation

[0036] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.

[0037] Example 1

[0038] Five rare earth co-doped zirconium oxide nanostructure ceramic materials Zr 0.88 (Gd 0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 and its preparation method:

[0039] In this embodiment, Zr is selected as the chemical composition. 0.88 (Gd 0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 The specific preparation process for using pentagonal rare-earth co-doped zirconium oxide as a ceramic material is as follows:

[0040] Step A1: Gd₂O₃, Yb₂O₃, La₂O₃, CeO₂, Y₂O₃, and ZrO₂ nanoparticles with a purity ≥99.9% and an average grain size <100 nm were mixed in a molar ratio of 1:1:1.5:3:1:88. 1 wt% polyvinyl alcohol (PVA) binder, 2 wt% ammonium citrate dispersant, and an appropriate amount of deionized water were added to control the slurry solid content to approximately 50 wt%. The mixture was then wet-milled using zirconia ball milling media at a ball-to-particle ratio of 2:1 at 600 rpm for 6 h to obtain a uniformly dispersed slurry.

[0041] Step A2: The slurry obtained in Step A1 is spray-dried using a spray dryer. During the process, the peristaltic pump speed is 35 rpm, the fan speed is 30 rpm, and the inlet air temperature is 240℃. The collected powder is dried at 80℃ for 12 hours until completely dry, and the particle size is controlled to be 38~75 μm through a 200~400 mesh sieve.

[0042] Step A3: The powder obtained in step A2 is solid-state synthesized at 1200℃ for 1 h to obtain a five-element rare earth doped zirconium oxide nanostructure ceramic material with the target microstructure and properties.

[0043] like Figure 1 As shown, the powder prepared according to the described process has a primary structure of spherical or apple-shaped particles, and a secondary structure that maintains a nanoscale structure. After passing through a 200-400 mesh sieve, the particle size is 38-75 μm, and the flowability is 130-150 s / 50g (refer to GB / T 1482-2022). Figure 2 As can be seen, the prepared pentagonal rare earth co-doped zirconium oxide phase is a single tetragonal zirconium oxide phase.

[0044] Example 2

[0045] The difference between this embodiment and Embodiment 1 is that Zr is used. 0.87 (Gd 0.03 Yb 0.03 La 0.03 Ce 0.03 Y 0.01 )O 1.95 Five rare-earth co-doped zirconium oxide was used as a ceramic material. In step A1, the molar ratio of Gd₂O₃, Yb₂O₃, La₂O₃, CeO₂, Y₂O₃, and ZrO₂ nanoparticles was 1.5:1.5:1.5:3:1:87. The morphology and phase composition of the material obtained in this embodiment are as follows: Figure 3 and Figure 4 As shown.

[0046] Example 3

[0047] Nanostructured thermal barrier coating Zr 0.88 (Gd0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 Preparation of TBC:

[0048] In this embodiment, nickel-based high-temperature alloy GH3230 is selected as the substrate of the thermal barrier coating system, NiCoCrAlY is selected as the adhesive layer attached to the substrate, and the pentagonal rare earth co-doped zirconium oxide powder prepared in Example 1 is selected as the powder for spraying the ceramic surface layer on the adhesive layer. The specific preparation process is as follows:

[0049] Step B1: Using high-temperature nickel-based alloy GH3230 as the substrate, NiCoCrAlY powder was sprayed using high-velocity plasma flame (HVOF) technology to form a bonding layer. The process parameters were: argon shielding gas flow rate 350±10 NLPM, methane / oxygen flow rates 175±5 NLPM / 245±5 NLPM respectively, nitrogen carrier gas flow rate 4 NLPM, powder feed rate 35±5 g / min, spraying distance 250±10 mm, and bonding layer thickness 116±8 μm.

[0050] Step B2: Ceramic surface layer preparation: Using the pentagonal rare earth doped zirconium oxide powder described in Example 1 as feedstock, an atmospheric plasma spraying process (current 600 A, voltage 73 V, main gas argon flow rate 42 SLPM, auxiliary gas hydrogen flow rate 12.5 SLPM, carrier gas argon flow rate 2.5 SLPM, powder feed rate 30 rpm) was used to spray the ceramic surface layer onto the adhesive layer surface, with a thickness of 207±10 μm, forming a complete coating system.

[0051] The thermal barrier coating structure prepared according to this method is as follows: Figure 5 As shown. The ceramic coating exhibits typical microstructural characteristics of atmospheric plasma spraying, with tight bonding between layers and no obvious cracks. The average porosity of the ceramic surface layer was calculated to be 10.253% by averaging the porosity of ten cross-sectional images under a 500x electron microscope. This porosity is particularly pronounced in the unmelted zone of the coating. Figure 5 b) The nanostructure was preserved. A conventional YSZ coating, with the chemical formula Zr, was prepared using the same process for comparison. 0.91 Y 0.09 O 1.955 .like Figure 6 As shown, the ceramic surface layers of both coatings in this embodiment exhibit a single tetragonal zirconia structure. Measurements show that the thermal conductivity and coefficient of thermal expansion of the traditional YSZ coating and the pentagonal rare-earth co-doped zirconia nanostructure coating materials are as follows: Figure 7 and Figure 8As shown in the figure. The results show that the thermal conductivity of the pentagonal rare-earth co-doped zirconium oxide prepared in this embodiment is only 1.09 W·m at 1000℃. -1 ·K -1 It is 38% lower than YSZ. The average coefficient of thermal expansion at 200~1200℃ is 10.92×10⁻⁶. -6 K -1 It is 2% higher than YSZ, and its coefficient of thermal expansion at 1200℃ is 11.34×10⁻⁶. -6 K -1 The fracture toughness is 4.58 ± 0.15 MPa·m. 1 / 2 .

[0052] Example 4

[0053] Nanostructured thermal barrier coating Zr 0.87 (Gd 0.03 Yb 0.03 La 0.03 Ce 0.03 Y 0.01 )O 1.95 Preparation of TBC:

[0054] The difference between this embodiment and Embodiment 3 is that in step B2, the ceramic surface layer uses the pentagonal rare-earth-doped zirconium oxide powder from Embodiment 2 as the feedstock. The thermal barrier coating structure in this embodiment is as follows: Figure 9 As shown. The adhesive layer thickness is 107±7μm, the ceramic surface layer thickness is 210±13μm, and the ceramic surface layer porosity is 12.254%. In the unmelted area of ​​the coating ( Figure 9 b) The nanostructure is preserved, and the ceramic surface layer phase is a single tetragonal phase ( Figure 10 The thermal conductivity of the pentagonal rare-earth co-doped zirconium oxide prepared in this embodiment is 1.05 W·m at 1000℃. -1 ·K -1 The average coefficient of thermal expansion at 200~1200℃ is 10.83×10⁻⁶. -6 K -1 The coefficient of thermal expansion at 1200℃ is 11.28 × 10⁻⁶. -6 K -1 The fracture toughness is 4.57 ± 0.15 MPa·m. 1 / 2 .

[0055] Example 5

[0056] Isothermal oxidation experiment:

[0057] Isothermal oxidation experiments were conducted using the pentagonal rare-earth co-doped zirconium oxide nanostructure thermal barrier coatings prepared in Examples 3 and 4, and the control YSZ nanostructure thermal barrier coating. The experimental procedure was designed with reference to HB 5258-2000, as follows: Figure 11 As shown, a lifting furnace was used for the experiment. The specific steps were as follows: the furnace temperature was stabilized at 1100℃, and the initial mass m0 of the coating sample was recorded. The sample was then placed in the furnace for heat preservation. Once the furnace temperature stabilized at the test temperature, timing was started. The sample was removed after 1 / 4 / 7 / 10 / 20 / 30 / 40 / 50 / 60 / 70 / 80 / 90 / 100 h of heat preservation. The macroscopic morphology of the coating surface was observed and photographed, and the sample was weighed and recorded as m. i When m i When the temperature is ≤m0, the coating fails, and the holding time at this point is the thermal oxidation lifetime of the coating. If the coating does not fail after 100 hours of holding time, the experiment ends. In this embodiment, both the pentagonal rare earth co-doped zirconium oxide nanostructure thermal barrier coating and the YSZ coating system did not fail after 100 hours of thermal oxidation. The coatings bonded well to the substrate and showed no peeling, as shown in the results. Figure 12 As shown in the figure. The growth rate of thermally grown oxide (TGO) in the three coatings after different holding times was calculated, and the results are as follows. Figure 13 As shown. Clearly, the synergistic effect of pentagonal rare earth co-doping effectively slows down oxygen diffusion, resulting in slower TGO growth in the coating, where Zr... 0.88 (Gd 0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 The average TGO growth rate of TBC was 1.26 mg·cm⁻¹. -2 The growth rate is only 78% of that of TGO in YSZ coating, which is beneficial to the long life of coating.

[0058] After holding at 1100℃ for 100 hours, the cross-sectional morphology of the three coatings is as follows: Figure 14 As shown. The average TGO thickness was calculated by measuring the equivalent thickness of TGO in 10 coating cross-sections. The results show that the TGO thickness of YSZ is 7.53 μm, which is close to the critical TGO thickness (8 μm) for coating failure, while Zr... 0.88 (Gd 0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 The TGO thickness of TBC is only 6.06 μm, which is 20% lower than that of YSZ. In the nano-region of the coating, the nanoparticles in the YSZ coating ( Figure 14 b) has grown to the submicron and micron scales, while the nanoparticles in the pentagonal rare earth co-doped zirconium oxide nanostructure coating ( Figure 14 d and 14f) remain at the nanoscale and have good resistance to sintering.

[0059] The XRD patterns of the three coatings after being kept at 1100℃ for 100h are as follows: Figure 15 As shown in the figure, the results indicate that a small amount of monoclinic (m-phase) zirconium oxide is produced after the YSZ coating is held at 1100℃ for 100 h. This transformation from tetragonal to monoclinic phase is accompanied by a 4% volume expansion, generating stress. Considering that the TGO of the YSZ coating is close to the critical TGO thickness for coating failure after 100 h, this phase transformation process will obviously accelerate the coating failure. In contrast, the pentagonal rare earth co-doped zirconium oxide nanostructure thermal barrier coating is stable after being held at 1100℃ for 100 h, indicating that the synergistic effect of pentagonal rare earth co-doping effectively stabilizes the lattice, ensuring the phase stability of the coating during long-term service at high temperatures, which is beneficial to the long lifespan of the coating.

[0060] The above results demonstrate that, compared with traditional YSZ materials, the pentagonal rare earth co-doped zirconium oxide nanostructure thermal barrier coating material provided by this invention has good high-temperature oxidation resistance, and its preparation cost is low, the preparation method is simple, and it is easy to realize industrial production and application.

Claims

1. A pentagonal rare-earth-doped zirconium oxide nanostructure ceramic material, characterized in that... The chemical formula of the ceramic material is Zr. 1-x (Gd,Yb,La,Ce,Y) x O 2-δ x = 0.12~0.15, meaning the total rare earth ion doping amount is 12~15 mol%, of which the doping amount of a single rare earth ion is not less than 1 mol%. Gd 3+ and Yb 3+ The doping amounts were 2~3 mol%, Y 3+ The doping concentration is less than 4 mol%, through Ce 4+ With Gd 3+ Yb 3+ La 3+ Y 3+ The charge difference regulates the oxygen vacancy concentration δ, the average grain size of the ceramic material is <100 nm, and the phase is a single tetragonal zirconium oxide.

2. The pentagonal rare earth-doped zirconium oxide nanostructure ceramic material according to claim 1, characterized in that... The chemical formula of the ceramic material is Zr. 0.88 (Gd 0.02 Yb 0.02 La 0.03 Ce 0.03 Y 0.02 )O 1.955 or Zr 0.87 (Gd 0.03 Yb 0.03 La 0.03 Ce 0.03 Y 0.01 )O 1.95 .

3. A preparation process for the pentagonal rare earth-doped zirconium oxide nanostructured ceramic material according to any one of claims 1-2, characterized in that... The process includes the following steps: Step A1, Slurry preparation: Gd2O3, Yb2O3, La2O3, CeO2, and Y2O3 nanoparticles are mixed into ZrO2 nanoparticles, and binders, dispersants, and deionized water are added. The mixture is then wet-milled using zirconia ball milling media to obtain a uniformly dispersed slurry. Step A2, spray drying: The slurry is spray dried using a spray dryer to obtain spherical or apple-shaped dry powder. The powder is then sieved after drying for subsequent solid-phase synthesis. Step A3, solid-state synthesis: The dried powder is sintered in an atmospheric atmosphere to obtain a five-element rare earth-doped zirconia nanostructure ceramic material. The primary structure of the five-element rare earth-doped zirconia nanostructure ceramic material is a spherical or apple-shaped structure, and the secondary structure maintains a nanoscale structure.

4. The preparation process of the pentagonal rare earth-doped zirconium oxide nanostructure ceramic material according to claim 3, characterized in that... In step A1, the purity of Gd2O3, Yb2O3, La2O3, CeO2, and Y2O3 nanopowders is ≥99.9%, and the average grain size is <100nm; the solid content of the slurry is 30~60 wt%; the binder is polyvinyl alcohol, added at 0.5~2 wt% of the total amount of nanopowders; the dispersant is ammonium citrate, added at 0.5~3 wt% of the total amount of nanopowders; the ball milling speed is 400~800 rpm, the time is 4~12 h, the ball-to-material ratio is 1~3:1, and the water-to-material ratio is 0.8~2:1; in step A2, the peristaltic pump speed is 30~50 rpm, the fan speed is 30~40 rpm, the inlet air temperature is 240~260℃, and the particle size after sieving is 38~75 μm; in step A3, the sintering temperature is 1200~1300℃, and the time is 1~2 h.

5. The preparation process of the pentagonal rare earth-doped zirconium oxide nanostructured ceramic material according to claim 4, characterized in that... The slurry has a solid content of 45-55 wt%; the amount of binder added does not exceed 1 wt%; and the amount of dispersant added is not less than 1 wt%.

6. A long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion, characterized in that... The thermal barrier coating comprises a substrate, a metal bonding layer formed on the surface of the substrate, and a ceramic surface layer formed on the metal bonding layer. The ceramic surface layer is composed of a pentagonal rare earth-doped zirconium oxide nanostructured ceramic material with the chemical formula Zr. 1-x (Gd,Yb,La,Ce,Y) x O 2-δ x = 0.12~0.15, meaning the total rare earth ion doping amount is 12~15 mol%, of which the doping amount of a single rare earth ion is not less than 1 mol%. Gd 3+ and Yb 3+ The doping amounts were 2~3 mol%, Y 3+ The doping concentration is less than 4 mol%, through Ce 4+ With Gd 3+ Yb 3+ La 3+ Y 3 + The charge difference regulates the oxygen vacancy concentration δ. The average grain size of the ceramic material is <100 nm, and the phase is a single tetragonal zirconium oxide. The ceramic surface layer exhibits a "dual-mode" structure consisting of an unmelted region that retains the nanostructure and a molten region that has been melted and recrystallized. The porosity is controlled at 10~15%.

7. The long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion according to claim 6, characterized in that... The substrate is composed of a high-temperature nickel-based alloy; the metal bonding layer is composed of NiCoCrAlY with a thickness of 100~120μm; and the ceramic surface layer has a thickness of 200~300μm.

8. A process for preparing a long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion as described in any one of claims 6-7, characterized in that... The process includes the following steps: Step B1, Preparation of substrate and adhesive layer: NiCoCrAlY powder is sprayed onto the substrate surface using supersonic flame spraying technology to form a metal adhesive layer; Step B2, Ceramic Surface Layer Preparation: Using pentagonal rare earth-doped zirconia nanostructured ceramic powder as feedstock, the ceramic surface layer is sprayed onto the surface of the adhesive layer using an atmospheric plasma spraying process to form a complete long-life nanostructured thermal barrier coating.

9. The preparation process of the long-life nanostructured thermal barrier coating with low thermal conductivity and high coefficient of thermal expansion according to claim 8, characterized in that... In step B1, the process parameters for supersonic flame spraying are: argon flow rate of shielding gas 340~360 NLPM, methane / oxygen flow rates 170~180 NLPM / 240~250 NLPM respectively, nitrogen flow rate of carrier gas 3~5 NLPM, powder feed rate 30~40 g / min, and spraying distance 240~260 mm; in step B2, the process parameters for atmospheric plasma spraying are: current 550~600 A, voltage 65~75 V, argon flow rate of main gas 40~42 SLPM, hydrogen flow rate of auxiliary gas 11~13 SLPM, argon flow rate of carrier gas 2~3 SLPM, and powder feed rate 20~30 rpm.

Citation Information

Patent Citations

  • Multi-element high-entropy doped zirconia-based ceramic material as well as preparation method and application thereof

    CN115124339A

  • Preparation method of ultrahigh-temperature EB-PVD thermal barrier coating

    CN119751060A